PENGELOLAAN WEBSITE BIDANG KEMAHASISWAAN UNIVERSITAS RIAU SEBAGAI MEDIA INFORMASI MAHASISWA - Ayun Prastiwi; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Riau University has had a student affairs website since 2014, created specifically to meet the information needs of Riau University students. Since its inception, the student affairs website has been the most active website at the University of Riau. As time went on, the website's activity decreased until finally it was declared inactive at the beginning of 2019. Therefore, researchers conducted a study aimed at knowing the process of managing the website and knowing the inhibiting factors in managing the website in the field of student affairs at the University of Riau as a student information media. This research used qualitative research methods. The subjects of this research consisted of five informants who were selected using purposive techniques. Data collection is done through in-depth interviews, observation, and documentation. Data analysis techniques in this research include data collection, data reduction, data presentation, and conclusions or verification. The data validity checking technique uses triangulation techniques. The results showed that the management of the Riau University student affairs website as a student information media was carried out with the POAC management function (planning, organizing, actuating, controlling). In the management process, several obstacles were found that originated from Human Resources (HR), technology, procedures, and documents. However, the most influential as an obstacle in the management of student affairs websites comes from his HR.